Preference of influenza vaccination among the elderly population in Shaanxi province, China - Minghuan Jiang; Pengchao Li; Xuelin Yao; Khezar Hayat; Yilin Gong; Shan Zhu; Jin Peng; Xinke Shi; Zhaojing Pu; Yifan Huang; Yu Fang (Taylor & Francis Group, 2021)
The influenza vaccination uptake rate is low in China. In the current study, we aimed to explore the preferences of influenza vaccination among the Chinese elderly. A discrete choice experiment design was performed to assess their preferences toward five influenza vaccination attributes, including vaccine effectiveness, duration of protection, severe adverse effects, vaccination cost, and vaccination recommendation source. A total of 144 participants aged over 60 years from three cities of Shaanxi province in China were surveyed. A mixed logit model was employed to analyze the data. The elderly population were found to prefer influenza vaccination with a longer duration of protection, followed by lower severe adverse effects, higher vaccine effectiveness, and recommended by healthcare providers. The vaccination cost was the least important attribute. The most considerable marginal willingness to pay for vaccination (CNY220.90) and the highest vaccination choice probability (83.70%) occurred when the duration of protection extended from 3 to 12 months. The present study's findings would inform decision-makers on implementing appropriate interventions for the increase of influenza vaccination coverage among the elderly in China.